2011
DOI: 10.1111/j.1600-0781.2011.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of the impact of a sun safety program on volunteers in outdoor venues

Abstract: Sun safety education could improve volunteer 's sun safety knowledge and behavior in the outdoor venues in China. Multi-component interventions proved to be the most effective sun safety education method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Some studies have reported increases in knowledge without an intention of, or actual, improvement in behavior [25]. In our previous study, the same phenomenon was observed [26]. We called this phenomenon a "knowledge-behavior gap."…”
Section: Discussionsupporting
confidence: 52%
“…Some studies have reported increases in knowledge without an intention of, or actual, improvement in behavior [25]. In our previous study, the same phenomenon was observed [26]. We called this phenomenon a "knowledge-behavior gap."…”
Section: Discussionsupporting
confidence: 52%
“…Following this, 655 records were excluded based on irrelevancy and duplicity, leaving a total of 46 papers to be examined. In addition, six studies were excluded because the intervention focused on health consequences of UV exposure (Cheng, Guan, Cao, Liu, & Zhai, ; Dykstra, ; Hernandez et al ., ; Lazovich et al ., ; Olson, Gaffney, Starr, & Dietrich, [included in the Williams, et al . () review]; Thomas et al ., ), three due to not examining relevant research questions (Cox et al ., ; Hillhouse, Turrisi, Stapleton, & Robinson, ; Walsh, Stock, Peterson, & Gerrard, ), and seven for not containing an intervention (Cheetham & Ogden, ; Hillhouse et al ., ; Noar et al ., ; Pagoto et al ., ; Taylor, Westbrook, & Chang, ; Welch, Chang, & Taylor, ; Williams et al., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The gap between sun safety knowledge/attitude and behavior was the focus of our previous study [10] and other studies [5,9]. It is generally believed that it is easier to increase sun safety knowledge than to change intended or actual sun safety behavior.…”
Section: Discussionmentioning
confidence: 94%
“…The questionnaire used in a previous sun safety study was used as a reference when preparing the questionnaires [10]. General instructions were provided by the same researcher before the survey that demonstrated how to fill out the questionnaire correctly.…”
Section: Methodsmentioning
confidence: 99%